Intimate partner violence practitioners’ understandings of wellbeing practices during the Covid-19 pandemic : a thesis submitted in partial fulfilment of the requirements for the degree of Masters in Science (Psychology) at Massey University, Aotearoa New Zealand - Christoffersen, Hannah (Massey University, 2023)
The Covid-19 pandemic signified an unprecedented global event with far-reaching consequences for individuals, communities and countries. Literature to date has explored the experiences of frontline healthcare workers—mainly doctors and nurses—during the pandemic, however the realities of how the pandemic impacted workers in other important support roles lacks coverage. This thesis aims to contribute to the dearth of research and literature on the everyday wellbeing of intimate partner violence (IPV) practitioners in the wake of the Covid-19 pandemic disruption. Providing care is an important aspect that is embedded in the work of IPV practitioners, but caring closely for and working with victim-survivors of IPV during the pandemic lockdowns was difficult with limited face-to-face interaction possible. This situation compromised IPV practitioners’ wellbeing. This narrative study is informed by phenomenology and feminist scholarly contributions of care ethics, and draws on the experiences of five IPV practitioners. Each participant undertook two semi-structured interviews, with the second interview based on photo-elicitation to explore their wellbeing practices during the pandemic. Prolonged lockdowns required IPV practitioners to work from home, which blurred the boundaries between work and home lives. Adjusting to this new reality, participants initially experienced apprehension and uncertainty how to best support and work with their clients. This period of transition impeded their ability to practice self-care and together with a high self-expectation to perform well under these altered circumstances diminished their sense of wellbeing. Overall this study demonstrates that wellbeing is holistic, fluid, and embedded in relationships with self, the environment, family and social networks. Participants demonstrate resilience and adapt to the changing conditions of everyday life. The findings also suggest the pervasiveness of norms and ideals such as those constituting ‘the good carer’ which pressure participants to neglect their self-care in an attempt to achieve unrealistic expectations. Introspection and resilience are key personal resources in addition to wider social relationships which nurture wellbeing and self-care.
Keywords: IPV practitioner; wellbeing; pandemic; everyday life; 520304 Health psychology